STUDIES ON PHYSICO-CHEMICAL PARAMETERS OF THE TWO COAL WASHERIES EFFLUENT NEAR DAMODAR RIVER OF DISTRICT BOKARO, JHARKHAND - ANJU KUMARI,; DR. RUPAM MALLIK, (The Bioscan, 2024)
The present investigation was carried out to assess the Physico- Chemical properties of two Coal washery effluent named Moonidih Coal washery and Dugda Coal washery of district Bokaro, Jharkhand, India. Water samples were collected on monthly basis from November 2021 to October 2022. A total 1 to 10 parameters were analysed by selecting the most practicable methods available in the Standard Method for examination of water and also waste water as per APHA, 2005. The average value of selected water parameters of Moonidih Coal washery and Dugda Coal washery, the temperature was 23.14°C. -24.51°C, Electrical conductivity (EC) 1035.33-800.6 µs/cm, Dissolved Oxygen (DO) 6.47-6.17mg/L, pH 8.23- 7.40, Total Dissolved Solids(TDS) 776.07-656.70 mg/L, Biological Oxygen Demand (BOD) 1.84-1.83 mg/L, Sulphate (So4) 55.0-56.31 mg/L, Nitrate (No3) 8.24-7.21 mg/L, Chloride (Cl-) 78.38-72.49 mg/L, Turbidity 29.55-24.43(NTU), respectively. Pearson’s correlation coefficient values show high significant positive and negative relationship (p<0.05 level). According to calculated WQI, 77.59 for Moonidih Coal Washery shows very poor-quality status and 55.19 for Dugda Coal Washery shows poor quality status as per Water Quality Index rating